The globular cluster system of NGC 1399. III. VLT spectroscopy and database - Dirsch, B. (2004)
Radial velocities of 468 globular clusters around NGC 1399, the central galaxy in the Fornax cluster, have been obtained with FORS2 and the Mask Exchange Unit (MXU) at the ESO Very Large Telescope. This is the largest sample of globular cluster velocities around any galaxy obtained so far. The mean velocity uncertainty is 50 km s-1. This data sample is accurate and large enough to be used in studies of the mass distribution of NGC 1399 and the properties of its globular cluster system. Here we describe the observations and the reduction procedure, and we discuss the uncertainties of the resulting velocities. The complete sample of cluster velocities that is used in a dynamical study of NGC 1399 is tabulated. A subsample is compared with previously published values.